Remifentanil Patient-Controlled Analgesia for Labor Analgesia at Different Cervical Dilations: A Single Center Retrospective Analysis of 1045 Cases - Tatjana Stopar Pintaric; Lara Vehar; Alex T. Sia; Tomislav Mirkovic; Miha Lucovnik (Medicina)
Background and Objectives: Remifentanil is a potent synthetic μ-opioid receptor agonist known for its rapid onset and ultrashort duration of action, making it a popular choice for intravenous labor analgesia. The analgesic effectiveness of remifentanil patient-controlled analgesia (Remifentanil-PCA) may vary based on the stage of labor and parity, potentially influencing satisfaction with labor analgesia. This study aimed to evaluate the degree of pain reduction achieved with remifentanil-PCA, considering different cervical dilations in both nulliparous and multiparous women. Material and Methods: Women who were ≥37 weeks pregnant with singleton cephalic fetuses, either by spontaneous onset or induction of labor, were included in the study. Data were collected from the Labor Record form, which included demographic and obstetric information, as well as the onset of analgesia categorized by cervical dilation (1–3 cm, 4–6 cm, 7–9 cm, and full dilation). Additionally, data on analgesia onset and duration (the time interval between the start of analgesia and the delivery of the baby), initial numerical rating scale (NRS0) for pain intensity, NRS after the first hour of analgesia (NRS1), the lowest recorded NRS during labor (NRSmin), and pain reduction during the first hour of analgesia (NRS0–VAS1), satisfaction with labor analgesia (rated 0 for dissatisfied, 1 for moderately satisfied, 2 for very satisfied), and complication rates were obtained from the remifentanil-PCA form. Results: A total of 513 nulliparas and 523 multiparas who gave birth between 1 January 2019 and 31 December 2019 were reviewed. No significant differences were found between the two groups regarding age, body mass index, labor induction rates, occipito-posterior positioning, blood loss > 500 mL, or neonatal outcomes. Nulliparas exhibited a higher gestational age (p = 0.021), longer labor duration (p < 0.001), and increased rates of cesarean sections (p < 0.001) and vacuum extractions (p = 0.002). Remifentanil-PCA consistently provided mild to moderate pain intensity reduction. No differences were found in VAS0, VAS1, or pain intensity reduction (VAS0–VAS1) regardless of the stage of labor or parity. Significant differences in VAS min were observed among nulliparas at different stages of labor (p < 0.026). However, a higher proportion of multiparas reported moderate (24.7% vs. 9.5%, p < 0.001) and high satisfaction (90% vs. 75%, p < 0.001) with remifentanil-PCA compared to nulliparas. Importantly, no serious complications in mothers or neonates attributed to remifentanil-PCA were observed during the observational period. Conclusions: Remifentanil-PCA demonstrates consistent effectiveness regardless of the stage of labor or parity. This indicates that remifentanil-PCA can be administered at any point during labor. Coupled with its rapid availability and immediate analgesic effect, this feature enhances the flexibility of its use in clinical practice.